FAKTOR PENENTU KEPUTUSAN PEDAGANG MUSLIM DALAM PEMILIHAN MODEL PEMBIAYAAN LEMBAGA KEUANGAN (STUDI PADA TEMPAT PELELANGAN IKAN (TPI) DI KOTA GORONTALO) - Napu, Iin Angraini; sofhian (MUTAWAZIN (Jurnal Ekonomi Syariah), 2021)
This study aims to determine the deciding factor ped decision a gang of Muslims in the fish auction Gorontalo province in the election financing financial instituted, with a sample of 68 respondents. This study uses multiple regression analysis tools on primary data. It is found that the traders' decisions have a positive and significant effect on marketing mix factors, socio-cultural factors, and psychological factors. The results of the correlation coefficient test for the Marketing Mix Factor, Socio- Cultural Factors, and Psychological Factors have a Pearson Correlation value of 0.986 this value proves that the Marketing Mix Factor, Socio- Cultural Factors, and Psychological Factors have a perfect correlation to the Decisions of Muslim Traders at Provincial Fish Auction Sites. Gorontalo . The coefficient of determination test results obtained the value of r 2 = 0.972. This value means that the variation of the independent variable can explain the dependent variable by 0.972 or it can be translated as 97.2 %, which means that 2.8 % is influenced by other factors not examined.